Resource Use Efficiency of Broiler Enterprises in Cross River State, South Eastern Nigeria - Etuk, E.A.; Agom, D.I.; Isika, M.A.; Idiong, I.C. (International Journal of Poultry Science, 2006)
A study was conducted to estimate broiler production functions based on data obtained from broiler enterprises around the Calabar municipality of Cross River State, South Eastern Nigeria. The data were analyzed using the mean difference model as well as the ordinary least square`s regression methods to estimate linear, double log, exponential and semi-log functions. The linear model provided the lead equations for the first four and second four weeks, while the double log model provided the lead equation for the entire eight weeks of rearing broilers. The study showed that the mean feed intake per bird, body mass gain and mortality rate of birds in the surveyed area differed (P< 0.05) significantly between the first and second four weeks of the rearing periods. The models revealed that 97, 92, and 98% of the total variations in broiler mass gain were selected explanatory variables during the study periods. In addition, feed intake and floor space affected (P< 0.05) mass gain positively, while mortality rate had a negative effect. The marginal value product (MVP) was more than the cost of 1kg of feed during the study period. It was concluded, that broilers production in the Calabar municipality required more feed and floor space to optimize mass gain, while the evident higher marginal value product compared to feed cost was indicative of irrational use of feed resource by farmers.